THE PARTICIPATION OF SPORT AS A SOCIO-CULTURAL PHENOMENON IN THE FORMATION OF MORAL QUALITIES OF A PERSON - Sherzod Azimov (Web of Journals Publishing, 2025)
This article examines the role of sport as a socio-cultural phenomenon in the formation of moral qualities in individuals. The research explores how participation in sports activities contributes to the development of ethical values such as discipline, respect, teamwork, and responsibility. Emphasis is placed on the educational and cultural functions of sport in shaping a morally conscious and socially active personality. The study also discusses the influence of traditional and modern sports practices on moral upbringing in different cultural contexts, particularly in the upbringing of youth in contemporary society.
Keywords: Sport, morality, socio-cultural phenomenon, ethical values, youth education, personal development, discipline, teamwork, cultural upbringing.